Evaluasi Tata Kelola Teknologi Informasi Menggunakan Kerangka Kerja Cobit dalam Mendukung Layanan Sistem Informasi Akademik Studi Kasus : Universitas Budi Luhur - Purwanto Purwanto (Universitas Budi Luhur, 2010)
Budi Luhur University has been implementing information technology (IT) in the management of academic information systems services. To create user loyalty, improve effectiveness and efficiency of resource use is required of an academic information system services are complete, accurate, current, complete, safe, consistent, timely and relevant. The role of IT in academic information systems Budi Luhur University can optimal if the application is well managed. IT governance can ensure a good way to evaluate the suitability of the application of IT with business needs, along with university identification of the risks of IT application and handling. This requires a standard model of representative governance and comprehensive, which covers issues of planning, implementation, operation and supervision of all IT processes. Related to the research of IT governance using the COBIT 4.0 (Control Objectives for Information and Related Technology) framework domain, especially the delivery & support and monitoring & evaluation to service the University academic information system Budi Luhur.